A phase IV, open-label three-arm study investigating the impact of a combination of tenofovir disoproxil fumarate/emtricitabine with raltegravir or dolutegravir or elvitegravir/cobicistat on renal function in HIV-1 antiretroviral naïve patients. Issue 5 (4th November 2021) - Bracchi, Margherita; Pagani, Nicole; Dalla Pria, Alessia; Milinkovic, Ana; Nwokolo, Nneka; Thomas, Lervina; Mandalia, Sundhyia; Boffito, Marta; Moyle, Graeme
Abstract : Objectives: Tenofovir DF (TDF) remains one of the preferred backbone agents for naïve HIV patients starting antiretroviral treatment (ART). The impact of TDF on renal function and metabolic parameters may vary by anchor agent. We investigated the impact of TDF in combination with 3 different integrase inhibitors on tubular and glomerular function, and metabolic parameters in ART-naïve patients. Methods: Sixty patients with normal renal function were randomised (20 per arm) to TDF/emtricitabine (FTC) plus either raltegravir (RAL) (400 mg b.d.), dolutegravir (DTG) or elvitegravir/cobicistat (EVG/c) for 48 weeks. Results: 57 patients completed the study. Significant increases in RBP/creatinine ratio at week 24 were seen in all arms [RAL +4.7 μg/mmol (CI 0.43 to 8.98, p = 0.032); DTG +4.96 μg/mmol (CI 0.77 to 9.15, p = 0.021); EVG/c +6.95 μg/mmol (CI 2.53 to 11.36, p = 0.002)], although this was not sustained to week 48 in the RAL arm. Similar changes across the arms were observed for urinary α1microglobulin (RAL +6.20 mg/L, p = 0.030; DTG +6.30 mg/L, p = 0.025; EVG/c +8.15 mg/L, p = 0.003). Urinary β2microglobulin significantly increased at week 24 with DTG and EVG/c but remained unchanged in the RAL arm. Glomerular filtration measured with CKD-EPI creatinine-cystatin C increased significantly in the RAL arm at week 24 through 48 but declined modestly in other two arms. Total and LDL cholesterol decreased in the RAL arm, but increased in the EVG/c arm, with no significant changes in the DTG arm. Weight increased significantly from baseline with DTG but not RAL or EVG/c. Conclusion: INSTIs in combination with TDF/FTC impact differently on tubular microproteinuria, eGFR, metabolic markers and weight. Use of TDF/FTC with RAL had the least tubular effects and the most favorable metabolic profile.